AI-Driven Gamified Learning in Cultural Heritage Education: A Conceptual Framework for Sustainable Civilization - I Made Pustikayasa (IAHN-TP Palangka Raya, 2026)
Cultural heritage education plays an essential role in preserving collective memory, strengthening cultural identity, and transmitting values across generations. In the digital era, however, conventional heritage learning often struggles to engage contemporary learners who are more accustomed to interactive, adaptive, and technology-mediated learning environments. This article proposes a conceptual framework for AI-driven gamified learning in cultural heritage education as a pedagogical response to this challenge. Drawing on relevant literature on artificial intelligence in education, AI scaffolding, gamified learning, instructional design, and culturally grounded learning, this conceptual study examines how AI and gamification may be meaningfully integrated to support heritage learning. The discussion suggests that artificial intelligence can provide adaptive support, personalized feedback, and scaffolding, while gamified learning can strengthen motivation, participation, and sustained engagement through challenge-based and interactive learning structures. The proposed framework positions heritage learning input as the cultural foundation of instruction, AI-driven adaptive support and gamified learning design as complementary enabling mechanisms, transformative learning as the pedagogical core, and proximal educational outcomes together with cultural sustainability-oriented outcomes as the expected results. This article argues that AI-driven gamified learning offers a plausible conceptual pathway for making cultural heritage education more engaging, reflective, and relevant for digital-age learners, while indirectly supporting the preservation and transmission of cultural values as part of a broader sustainability-oriented educational practice